FREE CURRICULUM THROUGH COMPASS BULOK GAME (LOCAL CULTURE) IN EARLY CHILDHOOD EDUCATION AT RA AMALIA DARMA SUNGGAL - Rozana, Salma; Widya, Rika; Rambe, Almanah (Proceeding International Seminar of Islamic Studies, 2024)
"Free Curriculum" is an innovative educational approach that encourages the development of creativity, skills, and character of students. One interesting approach in implementing the "Free Curriculum" is the use of educational games, such as "Local Culture Compass," which aims to connect students with local cultural heritage while facilitating enjoyable learning. This research proposes to investigate the phenomenon of implementing the "Free Curriculum" through the "Local Culture Compass" game in the context of education. The aim of this research is to explore the impact of the "Local Culture Compass" game in integrating the principles of the "Free Curriculum" into learning. This research will explore the perceptions of students and teachers regarding their experiences in using this game. Data collection methods will involve classroom observations, interviews, and document analysis. The collected data will be analyzed using an interpretative approach to identify key patterns in learning and teaching experiences. The results of this research are expected to provide deeper insights into the effectiveness of the "Local Culture Compass" game in implementing the "Free Curriculum." Additionally, this research will also produce practical recommendations for the development and implementation of the "Free Curriculum" through game-based approaches in the context of local culture. Thus, this research has the potential to make a positive contribution to advancing innovative education in Indonesia and promoting the preservation of local cultural heritage in the learning process.